The Effect of Flipped Classroom technique on Iraq EFL Students’ Achievement in Learning Adjectives - Salal, Assi. Prof. Saad; Ali, Assi. Instr. Bilal (مجلة أبحاث الذكاء, 2019)
The current study aimed at investigating the effect of flipped classroom technique on Iraq EFL students’ achievement in learning adjectives. The sample of the current study was 3rd grade students from the English Department at the college of Basic Education/ Al-Mustansiriyha University. To filful the aim of the study, the researcher adopted a null hypothesis which indicates that there was no significant difference between students’ achievement that used a new technique in learning adjectives of that do not use. To achieve the aim of the current study an eight weeks experiment was conducted on the experimental group with pre and posttest. The experiment was started on 11 October and ended in 11th January, 2017. At the end of the experiment, the researcher has used t-test for two groups and he submitted the form of the test to experts to ensure its validity and reliability, the calculated results had shown that there was a statistically significance difference between the achievement of the students of the experimental group on the posttest from control group. Finally, the researcher had put down some conclusions, recommendations and suggestions for further research.